THE ROLE OF ESTROGEN IN WOMEN WITH ANDROGENETIC ALOPECIA - Putu Diah Pratiwi; IGN Sri Wiryawan; Ni Made Linawati; Ni Luh Mas Rusyati (E-Jurnal Medika Udayana, 2013)
Hair loss may accured in both male and female population. Hair loss usually accured in Telogenic phase, meanwhile in Anagenic phase hair loss due to chemotherapy or radiation. Female pattern hair loss (FPHL) is regarded as hair fall type which is accured in women in common and known as female androgenetic alopecia. Almost 40%, 50 years old female shown hair fall sign, which is developed progressive fibrosing alopecia of central scalp, especially in frontal and parietal area. There are two common treatment for Female pattern Hair Loss are Minoxidil for topical use, and Fenesteride by oral. However, it has long been known that estrogens also profoundly alter hair follicle growth and cycling by binding to locally expressed high-affinity estrogen receptors (ERs), in turn increase anagenic phase and represed telogenic phase.